현미와 발아현미 증편의 품질특성에 관한 연구 - 서봉희(Bong-Hee Seo); 성기협(Ki-Hyub Sung); 정장호(Chang-Ho Chung) (東아시아食生活學會誌, 2011)
In this study, brown rice and germinated brown rice which has various medical action and excellent functionality, was used together with Jeung-pyun to compare and analyze the changes according to the amount 50, 100%. This study is intended to be used for the healthy food and spread to that was executed to find out the merchandising potential of this Jeung-pyun. The Jeung-pyun was added to brown rice and germinated brown rice of moisture content was 50.23~51.70% the similar to content. For chromaticity to L(lightness) value, a(redness) value and b(yellowness) value, L value of GBR2 was low at 58.84. a value was showed the highest GBR at 0.64. For texture, Hardness was showed the highest GBR2. Springiness was showed the highest BR2. Chewiness was showed the highest Control at 4.33. As for adhesiveness, there was showed the highest GBR2 at 0.30 and showed significant difference between samples. Overall-acceptability was the order of good in the estimated: GBR1>BR2>BR1>GBR2>C. Based on this study, from the physico-chemical and sensual perspective, For the preference of GBR1 was most preferred for flavor, color and taste, sensory evalution and considered suitable the best method for adding brown rice and germinated brown rice into Jeung-pyun.